BDNF secreted by mesenchymal stem cells improves aged oocyte quality and development potential by activating the ERK1/2 pathway - Jing Zhou; Cheng Li; Xin Mi; Jiali Zhou; Caiyi Chen; Jiayi Ren; Ran Liu; Gang Liu; Zi-Jiang Chen; Yingying Qin; Keliang Wu; Shidou Zhao (Cell Communication and Signaling)
Abstract Background Reduced oocyte quality is a key factor in age-related fertility decline, and there are no effective treatments available. The secretome of mesenchymal stem cells (MSC-sec) contains various bioactive factors and has the potential to improve oocyte quality. This study aimed to investigate the effective component and molecular mechanism of MSC-sec involved in improving oocyte quality from aged mice and humans. Methods Immunofluorescence and chromosome spread were performed to investigate the effects of secretome from human umbilical cord-MSC on spindle assembly and aneuploidy in aged mouse oocytes. Brain-derived neurotrophic factor (BDNF) and its neutralization antibody was supplemented in both in vitro and in vivo experiments to verify the effective component in MSC-sec. RNA-seq analysis was used to reveal the alterations in maternal mRNA degradation in aged mouse oocytes after MSC-sec treatment. In vitro culture of oocytes from aged women was also used to verify the effectiveness of BDNF in improving oocyte quality. Results MSC-sec treatment significantly increased first polar body emission, improved spindle assembly, promoted maternal RNA degradation, and reduced aneuploidy rate in aged mouse oocytes. While the addition of BDNF neutralization antibody blocked the effects of MSC-sec, BDNF alone also increased the oocyte quality from aged mice. Mechanistically, both MSC-sec and BDNF rescued the quality of aged mouse oocytes by activating the ERK1/2 signaling pathway to increase the expression of DAZL and BTG4. In situ injection of MSC-sec or BDNF into aged mouse ovaries significantly improved oocyte quality and early embryonic development. Finally, we demonstrated that BDNF treatment increased both the fertilization rate and blastocyst formation rate of aged human oocytes. Conclusion These findings demonstrate that BDNF secreted by mesenchymal stem cells can improve the quality and development potential of oocytes from both aged mice and humans by activating the ERK1/2 signaling pathway, suggesting that it has the potential to mitigate age-related declines in oocyte quality.